1998
DOI: 10.1046/j.1471-4159.1998.70010210.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accumulation and Increased Blood‐Brain Barrier Permeability to Circulating Alzheimer's Amyloid β Peptide in Aged Squirrel Monkey with Cerebral Amyloid Angiopathy

Abstract: Senescent squirrel monkey is a valuable model to study pathogenesis of cerebrovascular amyloid angiopathy (CAA). Cerebrovascular sequestration and bloodbrain barrier (BBB) permeability to 1251-amyloid~3(1 -40) synthetic peptide (sA/3 1_40) were studied in adult versus aged squirrel monkey 1 h after a single intravenous injection. In aged monkey, the half-time of elimination of sA/31_40, t~12, was prolonged by 0.6 h, the systemic clearance,~was reduced from 1.8 to 1.1 mI/mm/kg, and the mean residence time of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 23 publications
7
79
0
Order By: Relevance
“…Circulating Aβ is predominantly cleared by either degradation in hepatocytes or direct excretion in bile; several peptide clearance experiments have suggested that soluble Aβ has a short half-life of 2.5 min to 2.5 h in the circulation 26,107 . LRP1 is thought to mediate the uptake of Aβ by hepatocytes 25 .…”
Section: Hepatic Dysfunctionmentioning
confidence: 99%
“…Circulating Aβ is predominantly cleared by either degradation in hepatocytes or direct excretion in bile; several peptide clearance experiments have suggested that soluble Aβ has a short half-life of 2.5 min to 2.5 h in the circulation 26,107 . LRP1 is thought to mediate the uptake of Aβ by hepatocytes 25 .…”
Section: Hepatic Dysfunctionmentioning
confidence: 99%
“…170,171 In aged ( > 24 years) monkeys, systemic clearance of 125 IAb40 injected intravenously was significantly reduced compared to adult (aged 8-10 years) monkeys. 170,171 Conversely, BBB of aged monkeys was more permeable to 125 IAb40 than younger animals, with a higher sequestration of Ab within the cerebral vasculature and brain parenchyma. 170,171 Although small numbers of animals were used in these experiments, an age-dependent, selective effect on Ab transport across BBB was demonstrated.…”
Section: Ab Clearance Mechanismsmentioning
confidence: 99%
“…P=f- (15) By equations (12)- (13) (1) to zero and solving equations (1), (3) and (4) (12) and (14)- (16) (18) and (19) within hours after treatment, and then slowly approach their post-treatment steady states.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…levels experience a transient rise and then return to the pre-treatment levels. The return to pre-treatment levels follows from the fact that the fragmentation rate does not alter the steady-state brain monomer level in equation (12), which is the brain's only interaction with the CSF and plasma compartments. In contrast to the case of the production inhibitor in Figure 2, the values in equations (18) and (19) are quite different than the post-treatment steady-state levels in the CSF and plasma.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation